A Study on Recruitment Process in “Midland Microfinance Limited” at Jal - Nayia Sharma (International Journal of Engineering and Management Research, 2020)
Human Resources is the most valued and most treasured asset for any Organization. Best Outcome can be Judged with the efficient Recruitment and Selection strategies. The main objective of this paper is to streamline Recruitment process in Midland Microfinance Ltd at Jal. The study also focuses its attention to carry out and promote a fair and transparent recruitment procedure. The well-structured questionnaire was used for the data collection. The source of data was both primary and secondary. Data analysis has been done with statistical tools like tables, graphs, bar diagrams etc. With reference of to this context the research paper entitled Recruitment has been prepared to put light on Recruitment process. The main objective of the study is to Highlights on the most preferable method for recruitment, as well as To study various the sources used for recruitment in Midland microfinance limited company in Jalandhar.